KOMPARASI METODE QUANTUM TEACHING DENGAN MODEL PEMBELAJARAN PENDEKATAN SAINTIFIK TIPE PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR DASAR LISTRIK DAN ELEKTRONIKA DI SMKN 1 LINTAU BUO - Nur Rina Ritonga; Muhammad Anwar; Yasdinul Huda (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2018)
The efforts in order to find an effective methods to improve the students  learning outcomes are very important. The field assessment has conducted to class x student’s, department of Audio Video Engineering of SMKN 1 Lintau Buo depicting  students learning outcomes below minimum completeness criterium of 75. This research aims to compare applying Quantum Teaching Method to problem based learning (PBL) by using Quasi experiment with pre-test post-test control group design, the both of methods have compared with. Experiment class I by applied Quantum Teaching provides class mean score of 81.44, while experiment class II by applied PBL yields class mean score of 77.78. By using t-test, it can be described that Quantum Teaching is more effective than PBL  significantly. This is because if tscorebigger than ttable (2.06 > 2.03), and consequently H0 is rejected. Despite the both methods actually show the small difference, but however, The Quantum Teaching has proven better than PBL viewing from students learning outcomes. Keywords: Quantum Teaching, Problem Based Learning, Learning Outcomes, Experiment I, Experiment II, Comparison.